Pendidikan Karakter Anak Usia Dini Melalui Proyek Penguatan Profil Pelajar Pancasila Berbasis Budaya Lokal - Cornita, Juwita Mega Vira; Ma’arif, Nina Nuriya; Khasanah, Nur Fikriyatul (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
Early childhood education is a foundational stage that significantly influences children’s cognitive, emotional, and social development. This research investigates the application of a project-based learning approach aimed at reinforcing the Pancasila Student Profile by incorporating local cultural elements, particularly the damar kurung tradition, among group B learners at RA Walisongo Gresik. Employing a qualitative research design, the study found that learning activities rooted in the damar kurung culture contribute effectively to character formation, especially in nurturing cultural appreciation, collaboration, and a sense of responsibility. These values are manifested in the students’ enthusiasm, teamwork, and accountability during the damar kurung craft project. Furthermore, this approach deepens students’ knowledge and appreciation of Gresik’s local cultural heritage, with a specific focus on the damar kurung craft tradition.